The Tribe Dysoniini Part V: The group Paraphidniae, with Three New Species from Guatemala and Ecuador (Orthoptera: Tettigoniidae: Phaneropterinae) - Cadena Castañeda, Oscar J. (2016)
The moss-and-lichen mimic katydids of the group treated here are easily recognized by their long and slender wings held upward at an almost 45-degree angle. They live in rainforests of central and northern South America, with one species ranging southward to subtropical forest in NE Argentina. Here the recently introduced subgenus Anaphidna is raised to genus beside Paraphidnia, and three additional species are described: P. brevicristata n. sp. and P. tunki n. sp. from Ecuador, the latter along with the relatively complex male calling song, as well as A. obrieni n. sp. from Guatemala. P. gallina is redescribed. A key for the three species of Paraphidnia s. str. is included.